Determinants of Poverty In Indonesia - Nurul Azizah Az zakiyyah; Firsty Ramadhona Amalia Lubis; Intan Wahyuni Wahyuni (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2023)
This study aims to determine the effect of economic growth, unemployment, labor, human development index (HDI), and the provincial minimum wage on poverty in 34 provinces of Indonesia in 2018-2021. This study uses a quantitative approach method. The data used in this study is data from 34 provinces of Indonesia in 2018 – 2021. The analytical model used is a panel data regression analysis with a secondary Fixed Effect Model (FEM) approach.The results of the study with a significance level of 5% indicate that (1) simultaneously (together) the variables of economic growth, unemployment, labor, human development index, and the provincial minimum wage have a significant effect on poverty; (2) the economic growth variable has a positive and significant effect on poverty; (3) the unemployment variable has a positive and significant effect on poverty; (4) the labor variable has a negative and insignificant effect on poverty; (5) the human development index (HDI) variable has a negative and significant effect on poverty; (6) the variable of the provincial minimum wage has a negative and insignificant effect on poverty.